Specialized transcription factories within mammalian nuclei. - Pombo, A; Jones, E; Iborra, F; Kimura, H; Sugaya, K; Cook, P; Jackson, D (2000)
Recent evidence suggests that active RNA polymerases are concentrated in discrete 'factories' where they work together on many different templates. The evidence that such factories specialize in the transcription of particular groups of genes is reviewed.